Parasite species of the endangered Iberian wolf (Canis lupus signatus) and a sympatric widespread carnivore - Ana Figueiredo; Lucia Oliveira; Luís Madeira de Carvalho; Carlos Fonseca; Rita Tinoco Torres (International Journal for Parasitology: Parasites and Wildlife, 2016)
Parasites have a profound impact on wildlife population dynamics. However, until some years ago, studies on the occurrence and prevalence of wildlife parasites were neglected comparatively with the studies on humans and domestic animals. In this study, we determined the parasite prevalence of two sympatric wild canids: the endangered Iberian wolf (Canis lupus signatus) and the widespread red fox (Vulpes vulpes), in central Portugal. From November 2014 to July 2015, fresh fecal samples from both species were collected monthly in several transects distributed throughout the study area. All samples were submitted to several coprological techniques. In total, 6 helminth parasites (Crenosoma vulpis, Angiostrongylus vasorum, Toxocara canis, Trichuris vulpis, Ancylostomatidae, Toxascaris leonina), and a protozoa (Balantidium coli) were identified based on size and morphology. The red fox was infected by seven different parasites while the Iberian wolf was infected by four. All parasites present in wolf were also present in the red fox. C. vulpis had the higher prevalence in red fox, while Ancylostomatidae were the most prevalent parasites in wolf. To our knowledge, this is the first study in this isolated subpopulation of the Iberian wolf. Our results show that both carnivores carry parasites that are of concern as they are pathogenic to humans and other wild and domestic animals. We suggest that surveillance programs must also include monitoring protocols of wildlife; particularly endangered species.